Grip strength and cardiovascular drug use in older people: findings from the Hertfordshire Cohort Study. - Ashfield, T; Syddall, H; Martin, H; Dennison, E; Cooper, C; Aihie Sayer, A (2010)
BACKGROUND: reduced grip strength is associated with adverse health consequences, and there is interest in identifying modifiable influences. Cardiovascular drugs are commonly used by older people, but their effect on muscle strength is unclear. METHODS: we investigated associations between cardiovascular drug use and grip strength among 1,572 men and 1,415 women, aged 59-73, who participated in the Hertfordshire Cohort Study. RESULTS: Forty-five percent of participants were taking a cardiovascular drug. Furosemide was associated with average decreases in grip strength of 3.15 kg (95% confidence interval [CI] 0.90, 5.39, P < 0.01) among men and 2.35 kg (95% CI 0.93, 3.77, P < 0.01) among women after adjustment for age and height. Corresponding differences for nitrates were 1.84 kg (95% CI 0.29, 3.39, P = 0.02) among men and 3.66 kg (95% CI 1.99, 5.33, P < 0.01) among women. Calcium channel blockers and fibrates were associated with reduced grip among women. Statins were not associated with grip. The associations between grip strength and nitrate use in men and nitrate and fibrate use in women were robust to additional adjustment for co-morbidity. CONCLUSIONS: use of some cardiovascular drugs is associated with reduced grip strength in older people. These findings have potential implications for the functional ability of older people treated with these drugs.